Kinerja Satuan Pelaksana Badan Reintegrasi Aceh Kabupaten Aceh Tengah - Hajar Ashwad; Finta Kuhini (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Aceh Reintegration Boards based in the city of Banda Aceh and the extension of subordination at the district level is carried out by the Aceh Reintegration Agency implementing unit (SATPEL-BRA) in accordance with what is stated in Aceh Qanun Number 6 of 2015 concerning the Aceh Reintegration Agency article 1 number 15 which reads Reintegration Agency Implementing Unit Aceh Regency/City, hereinafter referred to as the BRA Regency/City Unit. The aim of this research is to find out the performance of SATPEL-BRA in Kab. Aceh is currently carrying out its main duties and functions in maintaining peace in Aceh, especially in the District. Central Aceh, the method used is descriptive qualitative by describing it in a detailed manner and data collection is carried out by in-depth interviews. The results of this research regarding the fulfillment of rights and the touch of programs have apparently not been effective enough, although various efforts have been made to improve the welfare of GAM combatants, political prisoners and political prisoners, but they have not been effective enough in terms of fulfilling justice for victims affected by the Aceh conflict, for example there are still cases Conflict victims still do not receive assistance from BRA, this is due to factors and obstacles such as limited budgets which hinder the optimal implementation of programs and activities. Lack of coordination between various related parties, both internal and external, causes inefficiency in carrying out tasks. Resistance from several parties to proposed changes or new innovations can hinder development and performance improvement. The policies taken by the central and regional governments greatly influence BRA's performance because the budget for the District Implementation Unit. Cities depend on whether or not there is a budget provided by the local government.